Characterization and Sources of Aromatic Hydrocarbons (BTEX) in the Atmosphere of Two Urban Sites Located in Yucatan Peninsula in Mexico - Cerón Bretón, Julia Griselda; Cerón Bretón, Rosa María; Vivas Ucan, Francisco; Barceló Baeza, Cynthia; Espinosa Fuentes, María de la Luz; Ramírez Lara, Evangelina; Rangel Marrón, Marcela; Montero Pacheco, Jorge Alfredo; Rodríguez Guzmán, Abril; Uc Chi, Martha Patricia (2017)
Abstract:Benzene,toluene,ethylbenzene,p-xylene,O3,NOx,CO,PM2.5 andmeteorologicalparameters were measured in urban air of two sites in Merida, Yucatan, Mexico during 2016–2017. Samples were collected using 1.5 h time intervals at three different sampling periods before being analyzed by gas chromatographywithﬂameionizationdetection. ThehighestconcentrationsofBTEXoccurredduring midday and afternoon in spring and summer seasons. Mean concentrations of, BTEX for the Cholul and SEDUMA sites, respectively, were 40.91 µg/m3 and 32.86 µg/m3 for benzene; 6.87 µg/m3 and 3.29 µg/m3 for toluene; 13.87 µg/m3 and 8.29 µg/m3 for p-xylene; and 6.23 µg/m3 and 4.48 µg/m3 for ethylbenzene. The toluene/benzene and xylene/ethylbenzene concentration ratios indicated that BTEX levels at both sites were inﬂuenced by local and fresh emissions (vehicular trafﬁc). Bivariate and multivariate analyses were performed in order to correlate BTEX concentrations with criteria air pollutants to infer their possible sources. Health risk assessment revealed that exposure to benzene exceeded the recommended value for the integrated lifetime cancer risk. These results suggest that Merida’s population is exposed to cancer risk, and changes in the existing environmental policies should therefore be applied to improve air quality. Keywords: volatile organic compounds; BTEX; tropospheric ozone; Merida; air pollution